2021
DOI: 10.1002/cncy.22495
|View full text |Cite
|
Sign up to set email alerts
|

Atypia of undetermined significance in thyroid cytology: Nuclear atypia and architectural atypia are associated with different molecular alterations and risks of malignancy

Abstract: BACKGROUND:The Bethesda System for Reporting Thyroid Cytopathology contains an atypia of undetermined significance (AUS) category with heterogeneous and distinct inclusion criteria. The purpose of this study was to investigate differences in malignancy rates and molecular alterations based on the presence of different criteria. METHODS: A laboratory information search was conducted to identify thyroid fine-needle aspiration specimens signed out as AUS. The cases were reclassified as architectural atypia (3A), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 29 publications
(40 reference statements)
2
29
0
Order By: Relevance
“…18 Data on the malignant fraction upon resection associated with the preoperative identification of THADA fusion across previously published studies (Table 2), including ours, ranged from 80%-100% if NIFTP is included and 32%-100% if NIFTP is excluded. 8,14,[19][20][21][22] The observed wide variation reflects the limitations shared by all of these studies: a small THADA fusion cohort size, selection bias of molecular testing on indeterminate nodules, and additionally, in our study, not all THADA fusion cases were resected, which can impact the malignant fraction estimate. Ultimately, larger studies with THADA fusion EFVPTC case that on resection demonstrated limited angioinvasion (<4 vessels).…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…18 Data on the malignant fraction upon resection associated with the preoperative identification of THADA fusion across previously published studies (Table 2), including ours, ranged from 80%-100% if NIFTP is included and 32%-100% if NIFTP is excluded. 8,14,[19][20][21][22] The observed wide variation reflects the limitations shared by all of these studies: a small THADA fusion cohort size, selection bias of molecular testing on indeterminate nodules, and additionally, in our study, not all THADA fusion cases were resected, which can impact the malignant fraction estimate. Ultimately, larger studies with THADA fusion EFVPTC case that on resection demonstrated limited angioinvasion (<4 vessels).…”
Section: Discussionmentioning
confidence: 87%
“…In a recent study by Glass et al exploring thyroid lesions classified as AUS with BSRTC, two THADA::IGF2BP3 fusion cases were included in their cohort, one of which was classified as AUS with architectural atypia (with encapsulated follicular variant of PTC on histologic follow-up) and one was classified as AUS with cytologic atypia (classified as NIFTP on histologic follow-up). 14 However, the specific cytomorphologic findings seen in these cases leading to the interpretation was not discussed. Nonetheless, similar to their study, our THADA-fusion thyroid lesions demonstrated variable degrees of nuclear atypia.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations